Patterns of Cervical Lymph Node Metastasis in Locally Advanced Supraglottic Squamous Cell Carcinoma: Implications for Neck CTV Delineation - Xu, Yi; Zhang, Ye; Xu, Zhengang; Liu, Shaoyan; Xu, Guozhen; Gao, Li; Luo, Jingwei; Huang, Xiaodong; Wang, Kai; Qu, Yuan; Zhang, Shiping; Liu, Qingfeng; et al. (Frontiers in Oncology, 2020)
Objective: To investigate the prevalence and distribution of cervical lymph node metastasis (LNM) in locally advanced supraglottic squamous cell carcinoma (LASCC) and guide the delineation of clinical lymph node target volumes. Materials/Methods: We reviewed patients defined as LASCC from Jan. 2000 to Dec. 2017 in our hospital. The primary tumor was operated on using partial or total laryngectomy, and all patients underwent bilateral neck dissection (level II–IV at least). Univariate and multivariate logistic regression were used to find risk factors associated with LNM. Results: A total of 206 patients were enrolled. In the whole group, the rate of ipsilateral metastasis (IM) was 60.9% (67), while contralateral metastasis was 25.5% (28) which associated with IM (p=0.001). 76 cases were diagnosed with clinical positive lymph nodes (cN+) and IM of unilateral lesions(n=49) was detected in levels II, III, and IV with LMRs of 73.5% (36), 63.3% (31), and 20.4 % (10), respectively, and contralateral metastasis of 36.7% (18), 16.3% (8), and 6.1% (3), respectively. Involvement of ipsilateral level II or III was associated with metastasis of ipsilateral level IV. A total of 130 cases had clinically negative neck lymph nodes (cN0). The prevalence of occult metastasis (OM) was 35.4%. The rates of OM to ipsilateral neck levels II, III, and IV were 21%, 11.1%, and 1.6%, respectively, while contralateral neck levels were 6.3%, 4.8%, and 0%, respectively. Histopathological differentiation was related to OM (p=0.003). 2 of 25 people were with level VIb metastasis and both of them were with subglottic involvement. Conclusion: Neck level II and III are most frequently involved and should be included in the high-risk CTV in cN+ patients. Level IV as a high-risk region should be included in CTV when ipsilateral level II or III are involved and as low-risk region when ipsilateral levels are not. In cN0 patients, contralateral neck may be included in low-risk CTV or even not irradiated taking in accounting of the pathologic differentiation.